Respuesta :

The answer would be -0.012345679.

The first thing you would do is substitute 3 in for x, seeing that you've told us x = 3. After you've substituted x, the equation would look something like:

f(3) = -3^-4. From here, all you have to do is solve! -3 to the power of -4 equals -0.012345679. Therefor, f(3) = -3^-4 equals -0.012345679

Answer:

- [tex]\frac{1}{81}[/tex]

Step-by-step explanation:

Using the rule of exponents

• [tex]a^{-n}[/tex] ⇔ [tex]\frac{1}{a^{n} }[/tex]

Hence

f(3) =- [tex]3^{-4}[/tex] = - [tex]\frac{1}{3^{4} }[/tex] = - [tex]\frac{1}{81}[/tex]